Organizational Climate and Work Motivation as Answer to Employee Performance Problems at PT. Kalmar Jaya Bandung - Yulius, Yopi (Journal of Law, Politic and Humanities, 2021)
The purpose of this study was to determine and analyze: (1) Organizational Communication Climate (2) Work Motivation; (3) performance; and (4) the influence of organizational communication climate and work motivation on employee performance at PT Kalmar Jaya Bandung, either simultaneously or partially. The research method used in this research is a descriptive survey and an explanatory survey, the unit of analysis in this study is the staff at PT Kalmar Jaya Bandung with a sample of 30 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of the study, it was found that the Organizational Communication Climate of the employees of PT Kalmar Jaya Bandung turned out to be giving good responses, the work motivation of the employees of PT Kalmar Jaya Bandung in general was good, the performance of employees of PT Kalmar Jaya Bandung was currently considered good. Organizational Communication Climate and Work Motivation simultaneously affect the performance of employees of PT Kalmar Jaya Bandung. However, partially, Organizational Communication Climate dominantly affects employee performance rather than work motivation. Because Organizational Communication Climate is more dominant in influencing performance, it becomes the first priority in improving employee performance. then employees of PT Kalmar Jaya Bandung are advised to consistently maintain the existing Organizational Communication Climate, so that they are able to work more professionally